1998
DOI: 10.1093/nar/26.15.3562
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of whole genome radiation hybrid mapping resources for non-mammalian vertebrates

Abstract: Radiation hybrid panels are already available for genome mapping in human and mouse. In this study we have used two model organisms (chicken and zebrafish) to show that hybrid panels that contain a full complement of the donor genome can be generated by fusion to hamster cells. The quality of the resulting hybrids has been assessed using PCR and FISH. We confirmed the utility of our panels by establishing the percentage of donor DNA present in the hybrids. Our hybrid resources will allow inexpensive gene mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 24 publications
5
70
0
Order By: Relevance
“…We determined the chromosomal positions of zebrafish D2 and D3 receptor genes by using the T51 radiation hybrid panel (Kwok et al, 1998). Gene map positions were calculated with the Zon RH mapper resource (http://zfrhmaps.tch.harvard.…”
Section: Chromosomal Mapping Of Zebrafish D2 and D3 Receptor Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the chromosomal positions of zebrafish D2 and D3 receptor genes by using the T51 radiation hybrid panel (Kwok et al, 1998). Gene map positions were calculated with the Zon RH mapper resource (http://zfrhmaps.tch.harvard.…”
Section: Chromosomal Mapping Of Zebrafish D2 and D3 Receptor Genesmentioning
confidence: 99%
“…Zebrafish dopamine receptor genes were mapped by using the Goodfellow T51 radiation hybrid (RH) panel (Kwok et al, 1998). The T51 panel was purchased from Research Genetics and made available to us by Dr. Keith Cheng (Department of Pathology, Penn State College of Medicine).…”
Section: Chromosomal Mapping Of Zebrafish Dopamine Receptor Genesmentioning
confidence: 99%
“…This map position is flanked by microsatellite markers z4760, z3334, and z1390 at 85.1 cM and z9871 at 93.7 cM. We attempted to confirm this linkage assignment by mapping atp1b2b on the T51 radiation hybrid (RH) panel (Kwok et al, 1998). We found that atp1b2b had an identical RH type to microsatellite marker z8122.…”
Section: Resultsmentioning
confidence: 94%
“…By using the T51 zebrafish-hamster somatic cell radiation hybrid (RH) panel (Kwok et al, 1998), zath3 was mapped to ϳ34 cM from the top of the linkage group (LG) 23 (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…T51 radiation hybrid panel (zebrafishhamster hybrid cell lines; Research Genetics; Kwok et al, 1998;Geisler et al, 1999) was used to map zath3. The following two primers were used (M1: 5Ј TCTGTATACTCTTGATGTCC 3Ј; M2: 5Ј ACTTTATGAGAATCGGTAGC 3Ј).…”
Section: Genome Mappingmentioning
confidence: 99%